2011
DOI: 10.1177/145749691110000103
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Therapies and Liver Transplantation in Acute Liver Failure; 10 Years of MARS Experience from Finland

Abstract: acute liver failure is a life-threatening condition in the absence of liver transplantation option. the aetiology of liver failure is the most important factor determining the probability of native liver recovery and prognosis of the patient. extracorporeal liver assist devices like Mars (Molecular adsorbent recirculating system) may buy time for native liver recovery or serve as bridging therapy to liver transplantation, with reduced risk of cerebral complications. Mars treatment may alleviate hepatic encepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Even if liver transplantation remains the only treatment for HRS, and even though the benefits of MARS on renal prognosis are controversial, some studies have assessed if MARS can be used as a bridge until liver transplantation. 30 Camus et al found, in an observational cohort study, that MARS dialysis helped gain time until liver transplantation for acute liver failure and was associated with a significantly higher spontaneous remission time. 31 This beneficial effect of MARS on survival, native liver recovery, and need for liver transplantation has been reported in acute liver-failure patients compared with standard medical treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if liver transplantation remains the only treatment for HRS, and even though the benefits of MARS on renal prognosis are controversial, some studies have assessed if MARS can be used as a bridge until liver transplantation. 30 Camus et al found, in an observational cohort study, that MARS dialysis helped gain time until liver transplantation for acute liver failure and was associated with a significantly higher spontaneous remission time. 31 This beneficial effect of MARS on survival, native liver recovery, and need for liver transplantation has been reported in acute liver-failure patients compared with standard medical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Even if liver transplantation remains the only treatment for HRS, and even though the benefits of MARS on renal prognosis are controversial, some studies have assessed if MARS can be used as a bridge until liver transplantation . Camus et al .…”
Section: Discussionmentioning
confidence: 99%
“…The two most frequent etiologies of ALF are either drug-induced or virus-driven. The overall mortality rate of ALF is estimated to be between 20% and 40% (Kantola et al, 2011). It is therefore not only important to efficiently identify this life-threatening condition as early as possible, but also to prevent the marketing of new chemical entities (NCE), that could lead to the onset of ALF.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality for patients with ALF is high because of multiorgan failure, sepsis, and severe brain edema . Liver transplantation (LT) remains the most effective treatment; the short‐term mortality rate for patients with severe ALF who receive modern treatment is approximately 20% to 40%, whereas in the pretransplant era, the mortality rate was as high as 82% . Extracorporeal albumin dialysis, such as the Molecular Adsorbent Recirculating System (MARS), can be used to treat and stabilize patients while they are waiting for a suitable donor graft for LT .…”
mentioning
confidence: 99%
“…Patients with deepening HE present with typical changes in brainwave patterns that can be detected with full‐montage electroencephalography (EEG), such as a general slowing of brainwave activity and the emergence of triphasic waves . The neurological changes are potentially reversible, and the progression of HE can be slowed with albumin dialysis . The neurological status of unconscious critical care patients should be monitored, but the gold‐standard method of an ICP‐sensitive catheter carries an increased risk of intracranial bleeding in ALF patients with an impaired coagulation status .…”
mentioning
confidence: 99%